Strategi Promosi Digital Pariwisata Indonesia Timur Berbasis Stand-Up Comedy pada Akun Instagram @bercandanyaindonesiatimur - Yansen Indiani; Suci Sandi Wachyuni; Dewi Ayu Kusumaningrum (Jurnal Ragam Pengabdian, 2026)
The increasingly competitive landscape of digital tourism promotion requires innovative communication strategies capable of attracting audiences and fostering emotional engagement. While social media has become an important tourism promotion platform, the use of stand-up comedy–based humorous content as a tourism communication strategy remains underexplored. This study aims to analyze the representation of tourism elements, messaging strategies, and forms of humor embedded in the Instagram account @bercandanyaindonesiatimur (BIT), as well as its potential as a tourism promotion medium. A qualitative approach employing qualitative content analysis was applied to videos, captions, and audience responses. The findings reveal that BIT effectively combines storytelling, local identity, and contextual humor to create authentic tourism narratives that strengthen destination image and increase audience engagement. Humor functions not only as entertainment but also as a persuasive communication strategy that shapes positive destination perceptions and stimulates visit intention. This study contributes to the development of digital tourism communication by demonstrating that humor-based user-generated content can serve as an effective and authentic tourism promotion strategy.